Dislocation clitique de l’objet à gauche en français écrit - Étienne Riou; Barbara Hemforth (Discours, 2015)
This paper deals with the acceptability of syntactic constructions in the light of a distinction between written and spoken French. We present this distinction as one factor within a multifactorial approach. Relevant factors include pragmatic, stylistic, and syntactic constraints which will influence the acceptability of an utterance. We therefore argue that, by modifying the information structure, it is possible to make a construction that is strongly associated with spoken French (clitic left dislocation of the object) acceptable in a written French context. To test this hypothesis, we present a series of experiments testing the construction’s acceptability under various informational constraints. We propose a model with similar constraints for both spoken and written French including modality as one of the predictors.